Recent Applications of Aminocatalysis in Reactions of α,β-Unsaturated Aldehydes - Mehta, Ronak; Chande, Vatsal Dhiraj; Appayee, Chandrakumar (Synlett, 2025)
Organocatalysis has gained prominence as a powerful tool in asymmetric synthesis, offering a metal-free and environmentally friendly route to enantioenriched molecules. Chiral secondary amines, particularly those derived from proline, have been especially effective, facilitating diverse carbon–carbon and carbon–heteroatom bond-forming transformations under mild conditions. This type of catalysis typically proceeds through two key mechanisms: enamine catalysis, which temporarily converts carbonyl compounds into nucleophilic enamines, and iminium catalysis, which increases the electrophilicity of α,β-unsaturated carbonyl compounds by forming reactive iminium ions. In particular, iminium catalysis has proven valuable for the enantioselective modification of electron-deficient alkenes, enabling important organic transformations. In this account, we summarize our recent advancements in asymmetric aminocatalysis, including the development of novel catalytic methodologies, innovative catalyst architectures, and their implementation in the enantioselective synthesis of biologically active compounds.
Keywords: Asymmetric catalysis; Organocatalysis; Iminium catalysis; Michael addition; Secondary amine catalysis; Bioactive molecules